Atomic-scale origin and multiscale evolution of non-electrochemical dissolution of metals in molten salts - Rui Yuan; Handong Jiao; Ruiyang Sun; Leyang Li; Qi Wang; Donghua Tian; Xuefeng Zhang; Dongbai Sun; Shuqiang Jiao (Journal of Materials Research and Technology, 2025)
Non-electrochemical dissolution (NED) of metals in melts is ubiquitous in daily life. Here, taking Ti dissolution in molten salts as an example, we decipher the mechanisms of NED of metals in molten salts. We discover that beyond the chemical dissolution, the unexpected physical dissolution appears in molten salts. The physical dissolution originates predominantly from atomic thermal fluctuations at elevated temperatures, which weaken metallic bonds and intensify ion collisions with the metal matrix. Moreover, preferential dissolution occurs not only at grain boundaries but also on a specific crystal plane, which is attributed to its stronger halide adsorption affinity. Furthermore, the synergistic interplay between preferential dissolution and residual stress release triggers the slip-dissolution process, causing the Ti surface morphology to gradually evolve into characteristic terraces and dents. The findings clarify the atomic-scale origin and multiscale evolution of NED of metals in molten salts, laying the foundation for precise regulation of metal dissolution.